La gestión del talento humano y su relación con el desempeño laboral en el Gobierno Autónomo Descentralizado Municipal de San Miguel de Bolívar, año 2024. - Arcos Sinchigalo Jairo Ariel (2025)
This research focuses on 'The management of human talent and its relationship with job performance in the Decentralized Autonomous Municipal Government of San Miguel de Bolívar, year 2024.' In a context where efficiency and effectiveness in public administration are fundamental, the management of human talent emerges as a key factor for achieving institutional objectives. The study aims to analyze how human talent management strategies impact the job performance of employees in this municipal entity. It explores the importance of practices such as training, motivation, and staff recognition, as well as their influence on productivity and job satisfaction. Through a methodological approach that combines the collection of qualitative and quantitative data, it is expected to identify areas for improvement in human talent management and propose recommendations that contribute to optimizing job performance in the Decentralized Autonomous Municipal Government of San Miguel de Bolívar. The findings of this research seek to provide a solid foundation for decision- making that promotes a more effective and engaged work environment. Keywords: Human Talent and Job Performance.